2020
DOI: 10.1186/s13033-020-00342-1
|View full text |Cite
|
Sign up to set email alerts
|

Is supported self-management for depression effective for adults in community-based settings in Vietnam?: a modified stepped-wedge cluster randomized controlled trial

Abstract: Background: This study tested the effectiveness of a supported self-management (SSM) intervention to reduce symptoms of depression among adults compared with enhanced treatment as usual in community-based and primary care settings in Vietnam. Methods:The cluster randomized trial included 376 adults in 32 communes in eight provinces. Eligible participants scored > 7 on the SRQ-20 depression scale. Patients with severe symptoms were excluded and referred to tertiary care. Randomization took place at the commune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
2
30
0
1
Order By: Relevance
“…Engagement of social collaborators (lay social workers) to deliver the SSM intervention has important implications for improving availability of, and access to, depression care in Vietnam. Despite the challenges identi ed here, the SSM intervention demonstrated signi cant improvement for patients (27). This model, involving social collaborators, can help ll a critical gap in care for mild to moderate depression in Vietnam and other low-resource contexts.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Engagement of social collaborators (lay social workers) to deliver the SSM intervention has important implications for improving availability of, and access to, depression care in Vietnam. Despite the challenges identi ed here, the SSM intervention demonstrated signi cant improvement for patients (27). This model, involving social collaborators, can help ll a critical gap in care for mild to moderate depression in Vietnam and other low-resource contexts.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have reported that trained non-specialist providers in primary care clinics helped to reduce depressive symptoms in adults (36) and improve outcomes for depression, post-traumatic stress disorder, and alcohol use disorder (37) in LMICs. The MAC-FI study demonstrated that, despite the challenges identi ed, lay social workers (social collaborators) can provide effective social support to improve mental health care via SSM to those with mild to moderate depression, with training and supervision from a social worker (27).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet there is substantial variation in their training and experience, scope of work, and remuneration resulting from a lack of regulation and accreditation. For the most part they are unsalaried, although some may receive stipends for carrying out certain tasks [ 27 ].…”
Section: Introductionmentioning
confidence: 99%